Trichoblastoma of the upper eyelid - Bahram Eshraghi; Hamid Riazi-Esfahani; Ramon Katoozpour; Pasha Anvari; Mehdi Mortazavi; Fahaimeh Asadi Amoli (Journal of Ophthalmic & Vision Research, 2017)
Purpose: To describe a case of trichoblsatoma on the eyelid. Case Report: A 45-year-old woman presented with a recurring mass on her upper right eyelid. Histopathological examination revealed well-circumscribed tissue composed of an aggregation of basaloid cells. Immunohistochemistry showed positive staining for CD34 and CD10. The patient underwent total excision of the recurrent mass. Conclusion: Although rare, trichoblastoma should be considered in differential diagnosis of skin masses of the eyelids.